2020
DOI: 10.1097/mbp.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth monitoring of a hypertensive elderly patient with the new VITASENIOR-MT system: a case study

Abstract: Telehealth technologies providing remote monitoring of health parameters are a promising approach for the management of arterial hypertension (AH) in the elderly.The VITASENIOR-MT platform was developed as a telehealth solution designed to contribute to improve the health condition and quality of life, promoting safe and independent living of the old adult. It is an 'internet-of-things'-based solution relying on the interaction of the old adult with a TV-set to record biometric parameters and to receive warnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Una forma de suplir los límites del uso, sería, por ejemplo, utilizar dispositivos sanitarios en el 'Internet de las cosas', ya que estos productos requieren que íntegramente se disponga de validez y fiabilidad precisas, lo que podría ser aplicado para investigaciones de comorbilidad en el uso de dispositivos wearables (Straiton, et al, 2018). Siguiendo este contexto, son destacables algunos estudios realizados en pacientes con enfermedades crónicas (Medina-Moreira, et al, 2018) y, más recientemente, en personas mayores hipertensas (Pereira, et al, 2020).…”
Section: Dispositivos De Monitorización De Saludunclassified
“…Una forma de suplir los límites del uso, sería, por ejemplo, utilizar dispositivos sanitarios en el 'Internet de las cosas', ya que estos productos requieren que íntegramente se disponga de validez y fiabilidad precisas, lo que podría ser aplicado para investigaciones de comorbilidad en el uso de dispositivos wearables (Straiton, et al, 2018). Siguiendo este contexto, son destacables algunos estudios realizados en pacientes con enfermedades crónicas (Medina-Moreira, et al, 2018) y, más recientemente, en personas mayores hipertensas (Pereira, et al, 2020).…”
Section: Dispositivos De Monitorización De Saludunclassified
“…Biometric collected data were analysed by the health professionals, who calculated the mean SBP (systolic blood pressure) and DBP (dystolic blood pressure) and visit-to-visit BP to infer abnormalities, and analysed weight trends. A case study reporting the added-value of the system is presented in [ 36 ]. Senior participants reported that they were satisfied with the usefulness of the system and that they used it without difficulty, showing interest in continuing to use it.…”
Section: Resultsmentioning
confidence: 99%
“…Telemonitoring programs allow healthcare providers to monitor patients' health status and provide timely interventions remotely. Studies have demonstrated that telehealth significantly improves clinical outcomes for chronic conditions such as hypertension and chronic obstructive pulmonary disease (COPD) [ 44 , 45 ].…”
Section: Reviewmentioning
confidence: 99%